Training Executive, Attention, and Motor Skills (TEAMS): A Preliminary Randomized Clinical Trial of Preschool Youth with ADHD - Halperin, Jeffrey M. (J Abnorm Child Psychol, 2020)
This preliminary randomized controlled trial compared Training Executive, Attention and Motor Skills (TEAMS), a played-based intervention for preschool children with attention-deficit/hyperactivity disorder (ADHD), to an active comparison intervention consisting of parent education and support (ClinicalTrials.gov Identifier: ). The primary aims were to gauge preliminary efficacy and assist in further development of TEAMS. Four- and 5-year-old children with ADHD were randomly assigned to receive TEAMS (N=26) or the comparison intervention (N=26) with blinded assessments by parents, teachers and clinicians ascertained pretreatment, post-treatment, and 1- and 3-months post-treatment. Changes in ADHD severity, impairment, parenting factors, and neuropsychological functioning over time as a function of treatment condition were assessed using the PROC MIXED procedure in SAS. Across most measures, significant main effects for Time emerged; both treatments were associated with reduced ADHD symptoms that persisted for three months post-treatment. There were no significant Treatment effects or Time x Treatment interactions on symptom and impairment measures, suggesting that the magnitude of improvement did not differ between the two interventions. However, significant correlations emerged between the magnitude of behavioral change, as assessed by parents and clinicians, and the amount of time families engaged in TEAMS-related activities during treatment. Across a wide array of parenting and neuropsychological measures, there were few significant group differences over time. TEAMS and other psychosocial interventions appear to provide similar levels of benefit. Play-based interventions like TEAMS represent a potentially viable alternative/addition to current ADHD treatments, particularly for young children, but more research and further development of techniques are necessary.